(untitled) (Mustansiria Dental Journal, 2025)
Background: Dental caries is a common disease among humans, and its significant impact underscores the need to promote the mineralization of early enamel lesions. Numerous materials have been investigated to enhance the mineralization of teeth. Casein phosphopeptides-amorphous calcium phosphate (CPP-ACP), a milk protein known for its effectiveness in mineralization of tooth.Aim of study: To assess CPP-ACP’s effect on the enamel microhardness of teeth treated with 5% sodium fluoride. Materials and Method: Forty extracted sound upper first premolars were utilized in the study. The teeth underwent a pH cycle, after which, 20 teeth were treated with a 5% sodium fluoride solution (NaF), while the remaining 20 to deionized water. All teeth were placed in artificial saliva for 24 hours and subsequently treated with 10% CPP-ACP for seven days. Enamel microhardness was evaluated before and after the artificial formation of caries-like lesions, following the application of 5% sodium fluoride and deionized water, and after the application of CPP-ACP on the previously treated groups.Results: It was found that 5% NaF significantly elevated the microhardness of the enamel after demineralization (P=0.000), the mean microhardness value post-demineralization was (119.11), while post-remineralization was (195.910) and following the application of CPP-ACP it became (226.100) which was also significant (P=0.025).Conclusion: CPP-ACP is an effective material for mineralizing early carious lesions alone, but it performs its best effect when combined with NaF.